Analisis kebijakan dan isu-isu hukum yang berkaitan dengan streaming musik dan platform digital - Anggi Novalga Suryanto, S.Pd, M.Sn (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
The music industry is undergoing major changes with the advent of new technologies in the form of music and digital platforms. This research focuses on the role of data analysis in architects' management decisions and analyzes the political and legal issues associated with this phenomenon. In addition, this study also considers the social and cultural impact of music technology, especially in the context of popular applications such as Spotify among Indonesian students. The research method used to investigate the above problems is qualitative research method. The results of this paper show that content customization in broadcast media can affect music preferences and create a certain music culture. In addition, this digital platform is supported with good sound quality and excellent customization features, showing its popularityamong Indonesian students. However, if a song is used without a clear understanding of copyright, legal issues, and the process of applying it can arise. In the context of broadcast media security, the research also addresses the cyber threats facing the broadcast industry, focusing on the need to strengthen security to protect user data and ensure things run smoothly. Some of the security features include data encryption, user account protection, permissions and access control, application security, and protection against DDoS attacks. Research describes government actions and policies to provide security and stability through various digital technologies. It is proposed to expand the definition of commercial space in the context of copyright law to include digital platforms. Analysis of the role of law is carried out to bridge the gap between technological developments and the current legal framework.